2004
DOI: 10.1074/jbc.m312660200
|View full text |Cite
|
Sign up to set email alerts
|

AGS3 and Signal Integration by Gαs- and Gαi-coupled Receptors

Abstract: AGS3-LONG and AGS3-SHORT contain G-protein regulatory motifs that interact with and stabilize the GDPbound conformation of G␣ i > G␣ o . AGS3 and related proteins may influence signal strength or duration as well as the adaptation of the signaling system associated with sustained stimulation. To address these issues, we determined the effect of AGS3 on the integration of stimulatory (G␣ s -mediated vasoactive intestinal peptide receptor) and inhibitory (G␣ i -mediated ␣ 2 -adrenergic receptor (␣ 2 -AR)) signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…A particularly important ancillary use of the GoLoco-insensitivity mutation will be to delineate a potential role for GoLoco motif proteins in 7TMR-mediated signal transduction. Gain-of-function studies suggest that GPSM1/AGS3 can modulate the cellular levels of G␣ subunits and thus indirectly affect 7TMR signal transduction (75); other studies have suggested that 7TMR signaling in vivo may be modulated by GPSM1 and GPSM2 function (76 -78). Application of the GLi mutant to such studies will surely provide biochemical and structural insights into the biological function of this important class of G␣ regulatory proteins.…”
Section: Volume 283 • Number 52 • December 26 2008mentioning
confidence: 99%
“…A particularly important ancillary use of the GoLoco-insensitivity mutation will be to delineate a potential role for GoLoco motif proteins in 7TMR-mediated signal transduction. Gain-of-function studies suggest that GPSM1/AGS3 can modulate the cellular levels of G␣ subunits and thus indirectly affect 7TMR signal transduction (75); other studies have suggested that 7TMR signaling in vivo may be modulated by GPSM1 and GPSM2 function (76 -78). Application of the GLi mutant to such studies will surely provide biochemical and structural insights into the biological function of this important class of G␣ regulatory proteins.…”
Section: Volume 283 • Number 52 • December 26 2008mentioning
confidence: 99%
“…COS7 or HEK293 cells were cultured and transfected as described previously (17). In brief, cells were suspended at 0.5-1.0 ϫ 10 5 cells/ml, and 1.0 (12-well plate), 2.0 (35-mm dish), or 10 ml (100-mm dish) was plated.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…The GST-TFE3 fusion protein was expressed in bacteria (Escherichia coli BL21; Amersham Biosciences) and purified on a glutathione affinity matrix. The GST fusion protein was eluted from the resin, and glutathione was removed by desalting to allow a solution-phase interaction assay (17). Protein interaction assays and immunoblotting were performed as described previously (17,29).…”
Section: Generation Of Glutathione S-transferase (Gst) Fusion Proteinmentioning
confidence: 99%
See 2 more Smart Citations